Knowledge and perception of medical students towards the use of artificial intelligence in healthcare - Hania Ahmer; Saad Bin Altaf; Hamza Mustufa Khan; Ibrahim Ahmad Bhatti; Salwan Ahmed; Sanah Shahzad; Sajida Naseem (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the knowledge and perception of medical students regarding the utility and applications of artificial intelligence in medicine. Methods: The cross-sectional study was conducted at the Shifa College of Medicine, Islamabad, Pakistan, from February to August 2021, and comprised medical students regardless of gender or year of studies. Data was collected using a pretested questionnaire. Differences in perceptions were explored relative to gender and the year of studies. Data was analysed using SPSS 23. Results: Of the 390 participants, 167(43.1%) were males and 218(56.9%) were females. The overall mean age was 20±1.65 years. There were 121(31%) students from the first year of studies, 122(31.3%) second year, 30(7.7%) from third year, 73(18.7%) from fourth year, and 44(11.3%) from the fifth year. Most participants 221(56.7%) had a good familiarity with artificial intelligence, and 226(57.9%) agreed that the biggest advantage of using artificial intelligence in healthcare was its ability to speed up the processes. In terms of gender of year of studies, there were no significant differences on both counts (p>0.05). Conclusion: Medical students, regardless of age and year of studies, were found to have a good understanding of the usage and application of artificial intelligence in medicine. Key Words: Artificial intelligence, Medical students, Education, Perception.